Innovative solutions to the 2D nonlinear Schrödinger model in mathematical physics - S. Z. Hassan; D. M. Alsaleh; Munerah Almulhem; R. A. Alomair; A. F. Daghestani; Mahmoud A. E. Abdelrahman (AIP Advances)
We utilize a cohesive methodology to obtain some new solitary wave solutions for the (2 + 1)-dimensional nonlinear Schrödinger equation (2D-NLSE). The solutions provided herein are significant for elucidating physical phenomena in various domains, including optical fibers, plasma media, and ocean waves. Furthermore, scientific computing would be used to illustrate the physical interpretation of nonlinear waves. Our study examines how 2D-NLSE wave solutions affect physical model characteristics such as group velocity dispersion, nonlinearity, and linear coefficients. These variables functioned to control the amplitude and wave phase of the optical solitary waves during transmission. Finally, the strategy provided here is applicable to many nonlinear systems and new energy trends in natural science.